A Preclinical Mice Model of Multiple Sclerosis Based on the Toxin-Induced Double-Site Demyelination of Callosal and Cerebellar Fibers - Ortiz-Cisternas, F; Pulgar-Sepulveda, R (BioMed Central Ltd, 2024)
Background: Multiple sclerosis (MS) is an irreversible progressive CNS pathology characterized by the loss of myelin (i.e. demyelination). The lack of myelin is followed by a progressive neurodegeneration triggering symptoms as diverse as fatigue, motor, locomotor and sensory impairments and/or bladder, cardiac and respiratory dysfunction. Even though there are more than fourteen approved treatments for reducing MS progression, there are still no cure for the disease. Thus, MS research is a very active field and therefore we count with different experimental animal models for studying mechanisms of demyelination and myelin repair, however, we still lack a preclinical MS model assembling demyelination mechanisms with relevant clinical-like signs. Results: Here, by inducing the simultaneous demyelination of both callosal and cerebellar white matter fibers by the double-site injection of lysolecithin (LPC), we were able to reproduce CNS demyelination, astrocyte recruitment and increases levels of proinflammatory cytokines levels along with motor, locomotor and urinary impairment, as well as cardiac and respiratory dysfunction, in the same animal model. Single site LPC-injections either in corpus callosum or cerebellum only, fails in to reproduce such a complete range of MS-like signs. Conclusion: We here report that the double-site LPC injections treatment evoke a complex MS-like mice model. We hope that this experimental approach will help to deepen our knowledge about the mechanisms of demyelinated diseases such as MS. © The Author(s) 2024.